2010
DOI: 10.4155/bio.10.139
|View full text |Cite
|
Sign up to set email alerts
|

Validated LC–MS/MS Methods for The Determination of Dapagliflozin, A Sodium-Glucose Co-Transporter 2 Inhibitor in Normal and ZDF Rat Plasma

Abstract: The validated assay was successfully applied to the quantitation of dapagliflozin in plasma in support of preclinical studies in both normal and diabetic rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 9 publications
3
54
0
Order By: Relevance
“…Previous studies reported that sensitivity was greater in negative ionization for C-glycoside and dapagliflozin, which is a SGLT2 inhibitor with a C-glycoside structure [9,10]. However, when the LC-MS/MS assay was being developed in this study, positive, negative ionizations were both evaluated, and sensitivity was higher in positive ionization than in negative ionization for ipragliflozin.…”
Section: Mass Spectrometrymentioning
confidence: 77%
See 1 more Smart Citation
“…Previous studies reported that sensitivity was greater in negative ionization for C-glycoside and dapagliflozin, which is a SGLT2 inhibitor with a C-glycoside structure [9,10]. However, when the LC-MS/MS assay was being developed in this study, positive, negative ionizations were both evaluated, and sensitivity was higher in positive ionization than in negative ionization for ipragliflozin.…”
Section: Mass Spectrometrymentioning
confidence: 77%
“…However, MF was different from 1.0 and the matrix in plasma interfered with the quantification of ipragliflozin by LC-MS/MS when this liquid-liquid extraction method was used. Aubry et al, have developed and validated a LC-MS/MS method to quantify dapagliflozin, a SGLT2 inhibitor, in rat plasma, and reported that the matrix effect was 0.6 [9]. To improve the quality of analysis of SGLT2 inhibitors by LC-MS/MS, further investigations and improvements in the assay may be required.…”
Section: Recovery and Matrix Effectmentioning
confidence: 95%
“…During the assay develpment, acetate or formate deprotonated adduct ions were constantly observed and were initially considered to impact the sensitivity of the assay negatively 18 . For the assays to support preclinical study and early clinical studies, the presence of formate or acetate in the mobile phase was intentionally avoided in order to prevent the formation of the adducts and their suppression on the deprotonated molecular ion formation 14,15,16,18 .…”
Section: Sglt2mentioning
confidence: 99%
“…These results indicate that there was no significant plasma lot-tolot difference in matrix effect, whereas slight matrix effect was observed in the low QC samples. In the analysis of dapagliflozin, an SGLT2 inhibitor, in rat plasma by Aubry et al (2010), the matrix effect was reported to be 0.6. Moreover, we developed the LC-MS/ MS method for the quantitative analysis of ipragliflozin in rat plasma, and the mean MF ranged from 1.11 to 1.50, whereas there was no significant lot-to-lot difference in matrix effects (Kobuchi et al, 2015).…”
Section: Recovery and Matrix Effectmentioning
confidence: 99%